Identity Dynamics and the Crisis of Women’s Roles Between Modernism and Capitalism: A Critical Analysis of Mission and Family Integrity - Ignasius Welerubun (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: This article discusses the role struggles and identity crises faced by contemporary women amid the tug-of-war between the demands of modernism and traditional roles. Historically, patriarchal narratives have dominated history, placing women in roles devalued by capitalist production systems, thus giving rise to a sharp dichotomy of roles: economically productive career women versus housewives burdened by domestic syndrome. Objective: This study aims to deconstruct this dichotomy through the framework of critical gender theory and reconstruct the meaning of women's mission as a normative resolution. Methods: The method used is a critical content analysis of discourses regarding women's identities and activities. Results: Key findings show that the ideal image of women today is diverse, overlapping, and even improvisatory, without a clear conceptual standardization. In response to this confusion, the concept of Mission is redefined holistically and non-locationally. It is not measured by its field of work (in the office or at home), but by the orientation of its goals: the improvement of the quality of life, wholeness, and harmony towards a happy and prosperous family. Conclusion: The implication of this redefinition is an emphasis on conscious and ethical decision-making anchored in family integrity. This study contributes a normative framework demonstrating that women's mission is not determined by the location of work but by its goal: the quality of life, wholeness, and family harmony. Successful mission execution requires adopting five key ethical pillars—openness, dialogue, communicativeness, honesty and loyalty, and responsibility—crucial to prevent family dysfunction caused by role instability.